A Study of the Dynamic Recrystallization Behavior of Ni‐Based Superalloy during Hot Power Spinning Based on Cellular Automaton. Issue 7 (27th December 2018) - Long, Jinchuan; Zhu, Ningyuan; Xia, Qinxiang; Cheng, Xiuquan
Abstract : A two‐dimensional cellular automaton (CA) model of microstructure evolution is developed to visually and quantitatively simulate and predict the dynamic recrystallization (DRX) behavior of a typical Ni‐based superalloy during hot power spinning. The high‐temperature plane strain compression test and hot power spinning experiment are carried out to verify the developed CA model, and results show that the flow stress can be well predicted and the simulated average grain sizes are in good accordance with the experimental ones. The evolution of DRX and dislocation density as well as influence of processing parameters on DRX during hot power spinning are simulated and discussed. It is found that the DRX nucleation starts at grain boundaries when a large thinning ratio of wall thickness is reached. With the increasing of thinning ratio, the growth of crystal nuclei and secondary nucleation occurs. Furthermore, the average grain size and DRX fraction are greatly influenced by the forming temperature and thinning ratio, while the average grain sizes decrease slightly with the increasing of roller feed rate. Abstract : A two‐dimensional cellular automaton model of microstructure evolution is developed to study the dynamic recrystallization (DRX) behavior of Haynes 230 alloy during hot power spinning. The predicted results conform well with that of high‐temperature plane strain compression test and hot power spinning experiment. The DRX mechanism of Haynes 230 alloy and influence of processing parameters on its DRX are obtained.